Method for improving oxidation resistance of nano silver powder
By performing water dispersion, vacuum suction filtration, organic solvent coating and airflow dispersion on the nano silver powder, a protective film is formed, which solves the problems of low purity and antioxidant properties of silver powder, and significantly improves the conductive properties of the silver electrode and the energy of the solar cell. Conversion efficiency.
Patent Information
- Application Number
- CN202411612653.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-01-07
AI Technical Summary
In the prior art, the purity and antioxidant properties of silver powder are low, which affects the performance and life of photovoltaic cells.
By adding nano silver powder to the aqueous dispersion and stirring and dispersing, vacuum filtration and coating in organic solvents, a protective film is formed, and the powder dispersion is improved through airflow dispersion, and finally drying is performed to improve the antioxidant performance.
It significantly improves the antioxidant performance of silver powder, improves the conductive properties of silver electrodes, enhances the energy conversion efficiency of solar cells, and has a simple process and no environmental pollution, making it suitable for industrial production.
Smart Images

Figure CN119259996A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of silver powder preparation, and in particular to a method for improving the anti-oxidation performance of nano silver powder. Background Art
[0002] In the manufacturing process of photovoltaic cells, silver powder is an important conductive material. The purity and antioxidant properties of silver powder are key factors affecting the performance of photovoltaic cells. Low-purity silver powder will lead to decreased battery performance. The oxidation of silver powder will directly affect the sintering performance of the electrode, resulting in weak sintering density and shortened battery life. Therefore, the surface of the silver powder needs to be treated.
[0003] The invention patent application with application publication number CN118595438A provides a silver powder modification method, comprising: adding the silver powder to be modified into a surface modifier solution for reaction to obtain a silver powder slurry, wherein the surface modifier in the surface modifier solution includes a fatty acid compound and an amine compound; and separating the modified silver powder from the silver powder slurry. However, the above application does not purify the silver powder, resulting in a low purity of the silver powder. Based on this, the prior art still needs to be improved. Summary of the invention
[0004] In view of this, the present invention provides a method for improving the antioxidant performance of nano silver powder, which can at least solve the technical problems of low purity and antioxidant performance of existing silver powder.
[0005] A method for improving the anti-oxidation performance of nano silver powder of the present invention comprises the following steps: S1, adding nano silver powder into a water dispersion, stirring and dispersing the nano silver powder so that the nano silver powder is more evenly dispersed in the water to obtain a silver powder dispersion; S2, vacuum filtering the silver powder dispersion to obtain a filter cake; S3, adding the filter cake into an organic solvent, stirring and dispersing, and adding a coating auxiliary agent, stirring to obtain a silver powder organic dispersion, which can form a protective film on the surface of the silver powder; S4, vacuum filtering the silver powder organic dispersion to obtain silver powder; S5, drying the filtered silver powder; S6, dispersing the dried silver powder by air flow to obtain modified silver powder.
[0006] In some embodiments, in step S1, the aqueous dispersion is an aqueous solution to which a surfactant is added, and the surfactant is any one of sucrose ester, lauryl alkanolamine phosphate, dodecyl diamine oxide, polyvinyl pyrrolidone, and sodium lauryl sulfate, or a mixture of any two thereof, and the weight ratio of silver powder: water: surfactant is 100:200~1000:0.1~0.5. The surfactant can reduce the interfacial tension between the silver powder and water, making the silver powder easier to disperse in water to form a uniform suspension. By adjusting the type and amount of the surfactant, the viscosity of the aqueous dispersion can be controlled to make it more suitable for specific application requirements.
[0007] In some embodiments, the weight ratio of silver powder: water: surfactant is 100: 300-700: 0.15-0.4.
[0008] In some embodiments, in step S3, the organic solvent is a mixture of any one or more of alcohol, isopropanol, butyl carbitol, toluene, and petroleum ether; and the weight ratio of the silver powder to the organic solvent is 100:50-300.
[0009] In some embodiments, the weight ratio of the silver powder to the organic solvent is 100:80-220.
[0010] In some embodiments, in step S3, the coating auxiliary agent is any one or more of thioglycolic acid, humic acid, stearic acid, and 2,6-di-tert-butyl-p-cresol, and the mass ratio of silver powder to the coating auxiliary agent is 100:0.2~2.5.
[0011] In some embodiments, the mass ratio of silver powder to coating auxiliary agent is 100:0.3~2.
[0012] In some embodiments, in step S5, the silver powder is placed in an oven for drying, the drying temperature is 50-130° C., and the drying time is 1 h to 8 h.
[0013] In some embodiments, the silver powder is dried at a temperature of 60-95° C. and a drying time of 1.5-6 hours.
[0014] In some embodiments, in step S6, the silver powder is dispersed by air flow using an air flow mill, the air flow dispersion pressure is 0.35-0.75 MPa, and the feed rate is 0.5-10 Kg / h.
[0015] In some embodiments, the air flow dispersion pressure is 0.4-0.7 MPa, and the feed rate is 1-6 Kg / h.
[0016] In some embodiments, in step S1, the particle size of the nano silver powder is greater than 0.10 μm.
[0017] The beneficial effects of the present invention are as follows: the present invention uses surface modification technology to prevent oxygen and moisture from corroding the internal silver, significantly improves the anti-oxidation performance of the silver powder, improves the conductivity of the silver electrode, and thus improves the energy conversion efficiency of the solar cell, making the battery more efficient. The modified silver powder of the present invention is subjected to two dispersion and filter press treatments, and the powder has good dispersibility, high purity, stable performance indicators, and is easy to industrialize, with a simple process and no environmental pollution. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only some embodiments of the present invention. For ordinary technicians in this field, other embodiments can be obtained based on these drawings without paying creative work.
[0019] Figure 1 A schematic flow chart of a method for improving the anti-oxidation performance of nano silver powder provided by one embodiment of the present invention; Figure 2 This is a microscopic morphology of the silver powder after modification treatment according to Example 1 of the present invention. DETAILED DESCRIPTION
[0020] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the embodiments of the present invention are further described in detail below in combination with specific embodiments and with reference to the accompanying drawings.
[0021] It should be noted that all expressions using "first" and "second" in the embodiments of the present invention are for distinguishing two non-identical entities with the same name or non-identical parameters. It can be seen that "first" and "second" are only for the convenience of expression and should not be understood as limitations on the embodiments of the present invention. The subsequent embodiments will not explain this one by one.
[0022] The present invention provides a method for improving the antioxidant performance of nano silver powder, such as Figure 1 As shown, the following steps are included: S1, adding nano silver powder into a water dispersion, stirring and dispersing, to obtain a silver powder dispersion; specifically, an ultrasonic stirrer can be used for stirring, so that the silver powder is more evenly dispersed in the water.
[0023] S2, vacuum filtering the silver powder dispersion to obtain a filter cake to remove excess water and impurities; S3, adding the filter cake into an organic solvent, stirring and dispersing, and adding a coating auxiliary agent, stirring to obtain a silver powder organic dispersion, which can form a protective film on the surface of the silver powder.
[0024] S4, vacuum filtering the silver powder organic dispersion to obtain silver powder; S5, drying the filtered silver powder; S6, dispersing the dried silver powder by air flow to obtain modified silver powder.
[0025] Compared with the prior art, the present invention uses surface modification technology to prevent oxygen and moisture from corroding the internal silver, significantly improves the anti-oxidation performance of silver powder, improves the conductivity of silver electrodes, and thus improves the energy conversion efficiency of solar cells, making the battery more efficient. The modified silver powder of the present invention is subjected to two dispersion and filter press treatments, and the powder has good dispersibility, high purity, stable performance indicators, and is easy to industrialize, with a simple process and no environmental pollution.
[0026] In some embodiments, in step S1, the aqueous dispersion is an aqueous solution to which a surfactant is added, and the surfactant is any one of sucrose ester, lauryl alkanolamine phosphate, dodecyl diamine oxide, polyvinyl pyrrolidone, and sodium lauryl sulfate, or a mixture of any two thereof, and the weight ratio of silver powder: water: surfactant is 100:200~1000:0.1~0.5. The surfactant can reduce the interfacial tension between the silver powder and water, making the silver powder easier to disperse in water to form a uniform suspension, which helps to ensure that the silver powder can be evenly distributed in subsequent processes (such as coating, spraying, etc.), thereby improving the quality and performance of the product. By adjusting the type and amount of the surfactant, the viscosity of the aqueous dispersion can be controlled to make it more suitable for specific application requirements.
[0027] In some embodiments, the weight ratio of silver powder: water: surfactant is 100: 300-700: 0.15-0.4, which is a preferred ratio. The obtained silver powder dispersion has more optimized dispersibility and anti-agglomeration performance.
[0028] In some embodiments, in step S3, the organic solvent is a mixture of any one or more of alcohol, isopropanol, butyl carbitol, toluene, and petroleum ether; and the weight ratio of silver powder to organic solvent is 100:50 to 300. An appropriate weight ratio helps to disperse the nano silver powder more evenly in the organic solvent, prevents particle agglomeration, and helps to maintain the stability of the silver powder organic dispersion, preventing the silver powder from settling or flocculating during storage and use.
[0029] In some embodiments, the weight ratio of silver powder to organic solvent is 100:80-220. This is a preferred ratio, and the obtained silver powder dispersion has better dispersibility and anti-agglomeration performance.
[0030] In some embodiments, in step S3, the coating auxiliary agent is any one or more of thioglycolic acid, humic acid, stearic acid, and 2,6-di-tert-butyl-p-cresol, and the mass ratio of silver powder to the coating auxiliary agent is 100:0.2~2.5. The coating auxiliary agent forms a protective film on the surface of the silver powder, which can effectively isolate oxygen in the air and other factors that may cause oxidation, and significantly improve the antioxidant properties of the silver powder. By adjusting the type and amount of the coating auxiliary agent, the particle size and morphology of the silver powder can be controlled to a certain extent.
[0031] In some embodiments, the mass ratio of silver powder to coating auxiliary agent is 100:0.3~2, which is a preferred ratio. The silver powder obtained according to this mass ratio has more significant effects in improving antioxidant performance, enhancing stability, improving dispersibility, improving bonding strength, optimizing optical effects, controlling particle size and morphology, reducing costs, and simplifying processes.
[0032] In some embodiments, in step S5, the silver powder is placed in an oven for drying at a temperature of 50 to 130° C. for a drying time of 1 to 8 hours. Through the drying process, moisture and other volatile substances in the silver powder can be quickly removed, thereby speeding up the production process. The dried silver powder can be directly used for subsequent processing or application, reducing waiting time.
[0033] In some embodiments, the silver powder is dried at a temperature of 60-95° C. and a drying time of 1.5-6 hours, which is a preferred range that allows for sufficient drying while avoiding excessive energy consumption.
[0034] In some embodiments, in step S6, the silver powder is dispersed by airflow using an airflow mill, the airflow dispersion pressure is 0.35-0.75 MPa, and the feed rate is 0.5-10 Kg / h. The high-speed airflow impact of the airflow mill can effectively break the agglomeration between the silver powder particles, so that the silver powder particles are more evenly dispersed. For subsequent applications, such as electronic slurries, conductive inks, etc., a more uniform coating and better performance can be provided. In addition, the airflow mill can achieve fine control of the silver powder particle size by precisely controlling the airflow pressure and feed rate, which helps to meet the specific requirements of the silver powder particle size in different application fields.
[0035] In some embodiments, the air flow dispersion pressure is 0.4-0.7 MPa, and the feed rate is 1-6 Kg / h. This is a preferred configuration, which can fully disperse the silver powder particles while avoiding excessive energy consumption.
[0036] In some embodiments, in step S1, the particle size of the nano silver powder is greater than 0.10 μm. When the particle size of the nano silver powder is larger, the agglomeration phenomenon between the particles is relatively less, which helps to improve its dispersibility in the organic solvent. At the same time, the larger particle size also helps to reduce the surface energy and reduce the mutual attraction between the particles, thereby further improving the dispersibility and stability.
[0037] In order to better illustrate this solution, several specific embodiments and comparative examples are provided below: Example 1 A method for improving the anti-oxidation performance of nano silver powder comprises the following steps: S1, primary dispersion of silver powder: weigh 10 kg of water, add 6 g of polyvinyl pyrrolidone, fully dissolve and obtain a water dispersion, add 2 kg of silver powder with a particle size of 200 nm into the water dispersion, stir and disperse with an ultrasonic stirrer for 3 h to obtain a silver powder dispersion; S2, filtering the silver powder once: placing the silver powder dispersion in step S1 on a Buchner funnel for filtering, and taking it out after filtering until there is no water on the surface to obtain a filter cake; S3, silver powder coating: place the filter cake in a stirring barrel, add 3.8 kg of a mixed solution of alcohol and isopropanol (mass ratio 1:1) and mix thoroughly, then add 10 g of stearic acid, stir and disperse for 2 h to obtain an organic dispersion of silver powder; S4, secondary filtration of silver powder: placing the silver powder organic solution on a Buchner funnel for filtration to obtain silver powder; S5, drying the silver powder: drying the silver powder in an oven at 75°C for 3h; S6, secondary dispersion of silver powder: the dried silver powder is dispersed by air flow mill, with a feed rate of 1.2 Kg / h and a feed pressure of 0.42 MPa.
[0038] Example 2 A method for improving the anti-oxidation performance of nano silver powder comprises the following steps: S1, primary dispersion of silver powder: weigh 10 kg of water, add 4.5 g of lauroyl alkanolamine phosphate, fully dissolve and obtain a water dispersion, add 2 kg of silver powder with a particle size of 200 nm into the water dispersion, stir and disperse with an ultrasonic stirrer for 3 h, and obtain a silver powder dispersion; S2, filtering the silver powder once: placing the silver powder dispersion in step S1 on a Buchner funnel for filtering, and taking it out after filtering until there is no water on the surface to obtain a filter cake; S3, silver powder coating: place the filter cake in a stirring barrel, add 3.4 kg of a mixed solution of isopropanol and toluene (mass ratio 2:1) and mix thoroughly, then add 12 g of thioglycolic acid, stir and disperse for 2 h to obtain an organic dispersion of silver powder; S4, secondary filtration of silver powder: placing the silver powder organic solution on a Buchner funnel for filtration to obtain silver powder; S5, drying the silver powder: drying the silver powder in an oven at 70°C for 3h; S6, secondary dispersion of silver powder: the dried silver powder is dispersed by air flow mill, with a feed rate of 1.2 Kg / h and a feed pressure of 0.42 MPa.
[0039] Example 3 A method for improving the anti-oxidation performance of nano silver powder comprises the following steps: S1, primary dispersion of silver powder: weigh 10 kg of water, add 6 g of polyvinyl pyrrolidone, fully dissolve and obtain a water dispersion, add 2 kg of silver powder with a particle size of 200 nm into the water dispersion, and stir and disperse it with an ultrasonic stirrer for 3 hours; S2, filtering the silver powder once: placing the aqueous dispersion of step S1 on a Buchner funnel for filtering, and taking it out after filtering until there is no water on the surface to obtain a filter cake; S3, silver powder coating: place the filter cake in a stirring barrel, add 3.8 kg of a mixed solution of alcohol and isopropanol (mass ratio 1:1) and mix thoroughly, then add 35 g of stearic acid, stir and disperse for 2 h to obtain an organic dispersion of silver powder; S4, secondary filtration of silver powder: placing the silver powder organic solution on a Buchner funnel for filtration to obtain silver powder; S5, silver powder drying: the filtered silver powder is placed in an oven at 75°C for 3 hours; S6, secondary dispersion of silver powder: the dried powder is dispersed by air flow mill, with a feed rate of 1.2 Kg / h and a feed pressure of 0.42 MPa.
[0040] Comparative Example 1 Undispersed original silver powder particles with a particle size of 200nm.
[0041] Comparative Example 2 No stearic acid was added during the silver powder coating process, and the other processes were consistent with those in Example 1.
[0042] 80 g of the silver powder of Examples 1 to 3 and Comparative Examples 1 to 2 were taken, and ground and dispersed in an organic carrier pre-mixed with 15 g of terpineol, 3.5 g of ethyl cellulose and 1.5 g of soybean lecithin, and rolled on a three-roll ceramic rolling mill, and printed into a 0.2 mm*600 mm circuit for sintering resistance test. In addition, 5 g of silver powder was pressed into a cylinder with a diameter of 5 mm at a pressure of 20 MPa, placed in an environment of 85° C. and 85% humidity for 72 h, and then taken out and dried in an oven at 120° C. The weight change rate was statistically calculated. The specific results are shown in Table 1: Table 1: Silver powder performance evaluation table:
[0043] It can be seen from Table 1 that the silver powder modified by the method provided in the embodiment of the present invention has good anti-oxidation performance and good conductive performance.
[0044] Figure 2This is a microscopic morphology of the silver powder after modification treatment, taking Example 1 as an example. It can be seen from the figure that the powder after modification treatment has good dispersibility and high purity.
[0045] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0046] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims.
Claims
1. A method for improving the antioxidant properties of nano silver powder, comprising the following steps: S1, adding nano silver powder into a water dispersion, stirring and dispersing the mixture to obtain a silver powder dispersion; S2, vacuum filtering the silver powder dispersion to obtain a filter cake; S3, adding the filter cake into an organic solvent, stirring and dispersing, adding a coating auxiliary agent, and stirring to obtain a silver powder organic dispersion; S4, vacuum filtering the silver powder organic dispersion to obtain silver powder; S5, drying the filtered silver powder; S6, dispersing the dried silver powder by air flow to obtain modified silver powder.
2. The method for improving the anti-oxidation performance of nano silver powder according to claim 1, characterized in that: In step S1, the aqueous dispersion is an aqueous solution to which a surfactant is added, and the surfactant is any one or a mixture of any two of sucrose lipids, lauryl alkanolamine phosphate, dodecyl diamine oxide, polyvinyl pyrrolidone, and sodium dodecyl sulfate, and the weight ratio of the silver powder: water: surfactant is 100:200~1000:0.1~0.
5.
3. The method for improving the anti-oxidation performance of nano silver powder according to claim 2, characterized in that: The weight ratio of the silver powder: water: surfactant is 100: 300-700: 0.15-0.
4.
4. The method for improving the anti-oxidation performance of nano silver powder according to claim 1, characterized in that: In step S3, the organic solvent is a mixture of any one or more of alcohol, isopropanol, butyl carbitol, toluene, and petroleum ether; and the weight ratio of the silver powder to the organic solvent is 100:50-300.
5. The method for improving the anti-oxidation performance of nano silver powder according to claim 4, characterized in that: The weight ratio of the silver powder to the organic solvent is 100:80-220.
6. The method for improving the anti-oxidation performance of nano silver powder according to claim 1, characterized in that: In step S3, the coating auxiliary agent is any one or more of thioglycolic acid, humic acid, stearic acid, and 2,6-di-tert-butyl-p-cresol, and the mass ratio of the silver powder to the coating auxiliary agent is 100:0.2~2.
5.
7. The method for improving the anti-oxidation performance of nano silver powder according to claim 6, characterized in that: The mass ratio of the silver powder to the coating auxiliary agent is 100:0.3~2.
8. The method for improving the anti-oxidation performance of nano silver powder according to claim 1, characterized in that: In step S5, the silver powder is placed in an oven for drying, the drying temperature is 50-130° C., and the drying time is 1 h-8 h.
9. The method for improving the anti-oxidation performance of nano silver powder according to claim 8, characterized in that: The silver powder is dried at a temperature of 60-95° C. and a drying time of 1.5-6 hours.
10. The method for improving the anti-oxidation performance of nano silver powder according to claim 1, characterized in that: In step S6, the silver powder is dispersed by air flow using an air flow mill, the air flow dispersion pressure is 0.35-0.75 MPa, and the feed rate is 0.5-10 Kg / h.
11. The method for improving the anti-oxidation performance of nano silver powder according to claim 10, characterized in that: The air flow dispersion pressure is 0.4-0.7 MPa, and the feed rate is 1-6 Kg / h.
12. The method for improving the anti-oxidation performance of nano silver powder according to claim 1, characterized in that: In step S1, the particle size of the nano silver powder is greater than 0.10 μm.
Citation Information
Patent Citations
Silver powder modification method and modified silver powder
CN118595438A